High-color-fastness color paste and processing technology thereof
By employing a composite resin system, a core-shell structured composite pigment, and a quaternary light-stabilized composition with a specific ratio, combined with precise processing technology, the problems of fading and chalking of traditional color pastes under ultraviolet irradiation have been solved, achieving high color fastness and stability, and improving the coating's resistance to light aging and service life.
Patent Information
- Application Number
- CN202511244180.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-02
- Publication Date
- 2025-11-25
AI Technical Summary
Traditional color pastes used in textile coatings often result in fading and chalking due to ultraviolet radiation, and their insufficient resistance to light aging affects the product's appearance and service life.
By employing a composite resin system, a core-shell structured composite pigment, and a quaternary light-stabilized composition in a specific ratio, high color fastness and stability are achieved through synergistic enhancement of UV protection capabilities and precise control of temperature, pH value, and stirring speed during processing.
It significantly improves the coating's resistance to light aging, extends its service life, maintains color stability and coating performance, and improves application performance and appearance quality.
Smart Images

Figure CN121006716A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of textile coating technology, and more specifically, to high color fastness color pastes and their processing technology. Background Technology
[0002] Color paste is a mixture containing pigments and a certain proportion of resins, solvents and other auxiliary components. In the field of textile coating technology, it is applied to the surface of the base fabric through padding, scraping or transfer coating processes to give textiles lasting color, pattern and functionality. Its core function is to provide high hiding power and uniform and stable hue to ensure that the coated fabric maintains color consistency in subsequent processing and use.
[0003] In industrial production, in order to achieve large-scale and efficient color coating, a medium that can uniformly disperse pigments and provide stable colors is needed. This is the medium for color paste. The use of color paste can simplify the color matching process, improve production efficiency, and at the same time ensure the consistency and quality of product colors.
[0004] However, traditional color pastes have obvious drawbacks in textile coating applications, especially in outdoor applications. Due to long-term exposure to ultraviolet rays, the coating is prone to fading and chalking, which reduces the product's appearance and service life. Summary of the Invention
[0005] To address the problem of insufficient lightfastness of existing color pastes, this application provides a high color fastness color paste and its processing technology.
[0006] In a first aspect, this application provides a high color fastness color paste, which adopts the following technical solution: A high color fastness color paste, comprising the following components by weight: 45-65 parts of composite resin system; 20-35 parts of core-shell structured composite pigment; 4-6 parts of quaternary light-stabilized composition; 1.5-3 parts of multifunctional dispersant; 2.5-5 parts of aziridine crosslinking agent; 0.8-1.5 parts of leveling control agent; 0.5-1 part of silicone defoamer; 20-30 parts of composite solvent; The composite resin system consists of epoxy acrylate, silicone-modified polyurethane, fluorinated acrylate, and modified polyurethane acrylate, with a mass ratio of 4-7:2-4:0.5-1.5:1-2. The core-shell structured composite pigment is iron oxide red or titanium dioxide sequentially coated with a nano-alumina layer and a composite layer composed of zirconium oxide and cerium oxide in a mass ratio of 1:0.3-0.6, and the surface is treated with γ-glycidyl etheroxypropyltrimethoxysilane, with a total coating layer thickness of 50-100 nm. The quaternary light-stabilizing composition consists of benzotriazole UV absorbers, benzophenone UV absorbers, hindered amine light stabilizers, and hindered phenolic antioxidants.
[0007] By adopting the above technical solution, the coating achieves high color fastness, excellent dispersibility, and good adhesion by using a composite resin system composed of epoxy acrylate, silicone-modified polyurethane, fluorinated acrylate and modified polyurethane acrylate, a core-shell structured composite pigment and a quaternary light-stabilized composition with a specific mass ratio.
[0008] Preferably, the mass ratio of benzotriazole UV absorber, benzophenone UV absorber, hindered amine light stabilizer and hindered phenolic antioxidant in the quaternary light-stabilized composition is 3.5-5:2.5-3.5:1.8-3:0.8-1.5.
[0009] By adopting the above technical solution, the color paste's ability to protect against ultraviolet rays is synergistically enhanced, thereby improving the coating's resistance to photoaging and color stability.
[0010] Preferably, the hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the hindered amine light stabilizer is poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol) ester.
[0011] By adopting the above technical solutions, this combination not only provides protection against ultraviolet rays, but also enhances the aging resistance of the coating through chemical and physical means, ensuring that the coating maintains its color and performance during long-term outdoor use.
[0012] Preferably, the composite solvent is composed of propylene glycol methyl ether acetate, isophorone and high-boiling-point aromatic solvent S-150A, with a volume ratio of 1-3:1:0.1-0.3.
[0013] By adopting the above technical solutions, not only are the workability and drying speed of the pigment improved, but the appearance quality and physical properties of the coating are also improved by adjusting the evaporation rate and surface tension, providing a good foundation for the preparation of high-performance coatings.
[0014] Secondly, this application provides a processing technology for a high color fastness color paste, which adopts the following technical solution: A processing technology for a high color fastness color paste includes the following steps: S1. Resin activation: Mix the composite resin system with a portion of the composite solvent, add a multifunctional dispersant and stir to dissolve; S2, Pigment Dispersion: Add core-shell structured composite pigments, heat and perform high-speed shear dispersion; S3, graded grinding: Primary grinding: Use 0.8-1.2mm zirconia beads, with a bead-to-material ratio of 1.2:1 to 1.8:1, and grind at 35-45℃ for 1.5-2.5 hours until the fineness is ≤15μm; Secondary grinding: In the initial stage of grinding, add aziridine crosslinking agent for crosslinking activation, replace with 0.3-0.5mm zirconia beads, and grind at 25-35℃ for 1.5-3 hours under the condition of adding pH adjuster to control pH 7.5-8.5; S4. Additive curing: Add the quaternary light stabilizer, leveling agent, silicone defoamer and remaining solvent, and cure at 600-800 rpm for 1-1.5 hours. S5. Vacuum degassing: Degas for 40-60 minutes under a vacuum of -0.095 to -0.1 MPa, and then filter through a 5-10 μm filter bag; S6. Stepped curing: Use programmed temperature rise for segmented heat preservation.
[0015] By adopting the above technical solutions, the entire processing technology ensures the high performance and stability of the pigment paste by precisely controlling parameters such as temperature, pH value, stirring speed and time.
[0016] Preferably, in step S1, the amount of the composite solvent used is 60-70% of the total solvent, the mixing temperature is 40-50℃, the stirring speed is 1000-1200rpm, and the processing time is 30-40 minutes.
[0017] By adopting the above technical solution steps, S1 provides a good foundation for the subsequent pigment dispersion and grinding steps, ensuring the high performance and stability of the pigment paste. In particular, by controlling the processing time, it plays a role in ensuring the full activation and stability of the composite resin system.
[0018] Preferably, in step S3, the pH adjuster added in the secondary grinding stage is 2-amino-2-methyl-1-propanol, and the amount added is 0.1-0.5% of the total weight of the pigment paste.
[0019] By adopting the above technical solution and through this precise pH adjustment, the secondary grinding stage can achieve finer pigment dispersion, providing a solid foundation for the preparation of high-performance, high-color-fastness coatings. By controlling the pH value, unnecessary chemical reactions between pigments and resins during the grinding process can be prevented.
[0020] Preferably, in step S3, both the primary grinding and the secondary grinding are carried out in a horizontal nano-sand mill, and a circulating cooling system is used to control the temperature rise of the grinding material to ≤5℃.
[0021] By adopting the above technical solutions, the horizontal nano-sand mill combined with the use of a circulating cooling system provides precise temperature control and efficient dispersion for the grinding process of the pigment paste, thereby ensuring the high performance and stability of the pigment paste.
[0022] Preferably, in step S2, the temperature is raised to 55-60℃, the dispersion speed is 1800-2200 rpm, and the processing time is 50-70 minutes.
[0023] By adopting the above technical solutions and through these precise controls, step S2 can ensure that the pigment is well dispersed in the composite resin system, laying a solid foundation for subsequent grinding and the final performance of the pigment paste.
[0024] Preferably, in step S6, the stepped curing process is as follows: in the first stage, the temperature is increased to 45°C at 1°C / min and held for 4 hours; in the second stage, the temperature is increased to 60°C at 0.5°C / min and held for 24-40 hours.
[0025] By adopting the above technical solution and through this phased, stepped curing process, the rate and extent of chemical reactions in the pigment paste can be effectively controlled, thereby optimizing the physical and chemical properties of the pigment paste.
[0026] In summary, this application has the following beneficial effects: 1. Because this application uses a quaternary light-stabilized composition with a specific mass ratio, the synergistic effect of the four components (benzotriazole, benzophenone, hindered amine, and hindered phenol) in ultraviolet absorption and free radical capture has achieved a significant improvement in the light aging resistance of the coating, thereby greatly improving its light fastness.
[0027] 2. In this application, a composite system of fluorinated acrylate and modified polyurethane acrylate is adopted to form a rigid-flexible interpenetrating network structure: the fluorinated segments reduce the intermolecular forces, thereby giving the coating dynamic slippage ability; the polyurethane carboxyl groups construct an interfacial hydrogen bond network, thereby strengthening the coating-substrate anchorage, thus achieving the effect of simultaneous optimization of flexibility and adhesion.
[0028] 3. In this application, by constructing an alumina / zirconium-cerium composite double-layer coating structure on the pigment surface and performing silanization treatment, the penetration path of corrosive media is blocked through a continuous and dense chemical inert interface. Therefore, the color paste maintains color stability in strong acid and strong alkali environments, significantly extending the service life of the coating. Attached Figure Description
[0029] Figure 1 This is a flowchart of a high color fastness type color paste processing technology provided in this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0031] Technical concept: Traditional pigments often suffer from fading and chalking of coatings due to prolonged exposure to ultraviolet light, resulting in insufficient resistance to photoaging. This is due to two main reasons: firstly, the pigments themselves have poor weather resistance; for example, uncoated iron oxide red / titanium dioxide is prone to photodegradation. Secondly, conventional single light stabilizers cannot fully cover ultraviolet absorption, leading to problems such as fading and chalking in the coating, thus reducing the product's aesthetics and lifespan.
[0032] This application improves the light aging resistance of color pastes in the following three aspects: 1. Using iron oxide red / titanium dioxide as the core, a nano-alumina layer and a zirconium oxide / cerium oxide composite layer are sequentially coated. The alumina layer isolates the pigment from the resin, reducing photocatalytic degradation. The zirconium oxide / cerium oxide layer blocks ultraviolet rays through UV shielding and scattering. The surface is treated with γ-glycidyl etheroxypropyltrimethoxysilane to enhance the compatibility of the pigment-resin interface.
[0033] 2. Benzotriazole UVA, benzophenone UVA, hindered amine HALS and hindered phenolic antioxidants are compounded in a specific ratio to form a four-level protection; among them, benzotriazole and benzophenone broaden the UV absorption band to the full spectrum; HALS inhibits the photo-oxidation chain reaction; hindered phenols block the thermal oxidative degradation pathway, and the four components achieve synergistic protection through functional complementarity.
[0034] 3. The coating uses epoxy acrylate and silicone-modified polyurethane as the main chain, and introduces fluorinated acrylate and modified polyurethane acrylate. The four components are optimized and balanced in a mass ratio of 6:3:1:1.5 to balance the mechanical strength and weather resistance of the coating.
[0035] Preparation Example 1 I. Raw Material Composition of Core-Shell Composite Pigments 100g of iron oxide red with a particle size of 200nm, 0.1M aluminum sulfate solution, 12.9g of zirconium oxychloride octahydrate, 5.8g of cerium nitrate hexahydrate with a molar ratio of 1:0.45, and γ-glycidyl etheroxypropyltrimethoxysilane.
[0036] II. Preparation process of core-shell structured composite pigments S1, Nano-alumina coating S1.1 and 100g of iron oxide red were dispersed in 1.8L of deionized water and ultrasonically treated at 500W for 30min to form a 5wt% suspension; S1.2 Add 0.1M Al2(SO4)3 solution dropwise at a rate of 1mL / min until pH = 6.0, react at 80℃ for 2h, and stir mechanically at 300rpm. S1.3, perform heart separation at 8000 rpm for 10 min, wash with water until conductivity ≤ 50 μS / cm, dry at 110℃ for 6 h to obtain Al2O3 coating layer; S2, Zirconia / Cerium Oxide Composite Coating S2.1. Disperse the product of S1 in 1.5L of ethanol-water 1:1 mixture and sonicate for 20min. S2.2 Add ZrOCl2·8H2O and Ce(NO3)3·6H2O, add ammonia water dropwise at 2 mL / min until pH = 9.0, and react at 75℃ for 4 h; S2.3. Collect the solid by centrifugation, wash it three times with ethanol, and calcine it at 550℃ for 2 hours at a heating rate of 5℃ / min to form a ZrO2 / CeO2 composite layer with a thickness of 48±5nm.
[0037] S3, Alkane Surface Treatment S3.1. Immerse the product of S2 in a 3wt% silane ethanol solution with a solid-liquid ratio of 1:10. S3.2, react at 60℃ with stirring at 200 rpm for 1 hour; S3.3 After centrifugation, vacuum dry at 80℃ for 4 hours.
[0038] In this application: The epoxy acrylate was purchased from Jiangsu Sanmu Group Co., Ltd., brand name SM-6102; The silicone-modified polyurethane was purchased from Zhejiang Huafeng Group Co., Ltd., brand name HF-8805S; The fluorinated acrylate was purchased from Zhejiang Transfar Group Co., Ltd., brand name TF-501F; The modified polyurethane acrylate was purchased from Jiangsu Sanmu Group Co., Ltd., brand name SM-6235.
[0039] This application provides high color fastness color pastes and their processing technology. The high color fastness color pastes and their processing technology provided in the embodiments of this application are described in detail below.
[0040] According to a first aspect of this application, this application provides a high color fastness color paste, comprising the following components by weight: 45-65 parts of composite resin system; 20-35 parts of core-shell structured composite pigment; 4-6 parts of quaternary light-stabilized composition; 1.5-3 parts of multifunctional dispersant; 2.5-5 parts of aziridine crosslinking agent; 0.8-1.5 parts of leveling control agent; 0.5-1 part of silicone defoamer; 20-30 parts of composite solvent; The composite resin system consists of epoxy acrylate, silicone-modified polyurethane, fluorinated acrylate, and modified polyurethane acrylate, with a mass ratio of 4-7:2-4:0.5-1.5:1-2. The core-shell structured composite pigment is iron oxide red or titanium dioxide sequentially coated with a nano-alumina layer and a composite layer composed of zirconium oxide and cerium oxide in a mass ratio of 1:0.3-0.6, and the surface is treated with γ-glycidyl etheroxypropyltrimethoxysilane, with a total coating thickness of 50-100 nm. The quaternary light-stabilizing composition consists of benzotriazole UV absorbers, benzophenone UV absorbers, hindered amine light stabilizers, and hindered phenolic antioxidants.
[0041] Specifically, the composite resin system enhances the adhesion and weather resistance of the color paste, thereby improving the overall performance of the coating; the core-shell structured composite pigment improves the dispersion stability and resistance to chemical erosion, thus enhancing the color vibrancy and weather resistance of the coating; the quaternary light-stabilizing composition absorbs ultraviolet light and captures free radicals, thus delaying photoaging and color change of the coating; the introduction of multifunctional dispersants promotes uniform dispersion of pigments in the resin system; the addition of aziridine crosslinking agents forms a three-dimensional network structure in the resin system, thereby improving the mechanical strength and chemical resistance of the coating; the addition of leveling agents regulates the surface tension and flow behavior of the coating; the addition of silicone defoamers reduces bubbles and prevents pinholes during coating preparation; and the selection of appropriate composite solvents regulates the viscosity and flowability of the color paste, thereby optimizing the coating's application performance and drying speed.
[0042] The mass ratio of benzotriazole UV absorber, benzophenone UV absorber, hindered amine light stabilizer and hindered phenolic antioxidant in the quaternary light-stabilized composition is 3.5-5:2.5-3.5:1.8-3:0.8-1.5.
[0043] Specifically, this particular mass ratio optimizes the synergistic effect between the components, enabling the pigment to more effectively absorb ultraviolet light, capture free radicals, and prevent oxidation reactions when exposed to ultraviolet radiation, thereby extending the service life of the coating and maintaining its initial color.
[0044] The hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the hindered amine light stabilizer is poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol) ester.
[0045] Specifically, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] has strong antioxidant properties, which can capture free radicals and prevent the coating from oxidative degradation, thereby protecting the coating from aging caused by light and heat, and maintaining the coating's long-term color vibrancy and performance stability; poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol) ester has a highly efficient light stabilizing effect, which can absorb ultraviolet rays and quench excited-state molecules, thereby reducing photochemical damage to the coating caused by ultraviolet rays and extending the coating's service life.
[0046] The composite solvent consists of propylene glycol methyl ether acetate, isophorone, and high-boiling-point aromatic solvent S-150A, with a volume ratio of 1-3:1:0.1-0.3. Specifically, propylene glycol methyl ether acetate is the main solvent, which dissolves the resin and pigments, and adjusts the viscosity and flowability of the color paste, thereby optimizing the coating's application performance and drying speed. Isophorone is the reactive diluent, which reduces the viscosity of the color paste and improves the dispersion of the pigments, thereby improving the leveling of the coating and reducing defects such as pinholes and bubbles. The high-boiling-point aromatic solvent S-150A is the auxiliary solvent, which adjusts the evaporation rate and drying time of the color paste, thereby controlling the surface tension of the coating and improving its appearance and gloss.
[0047] According to a second aspect of this application, this application provides a processing technology for high color fastness color paste, which adopts the following technical solution: See appendix Figure 1 A processing technology for a high color fastness color paste, used in the above-mentioned high color fastness color paste, includes the following steps: S1. Resin activation: Mix the composite resin system with a portion of the composite solvent, add a multifunctional dispersant and stir to dissolve; S2, Pigment Dispersion: Add core-shell structured composite pigments, heat and perform high-speed shear dispersion; S3, graded grinding: Primary grinding: Use 0.8-1.2mm zirconia beads, with a bead-to-material ratio of 1.2:1 to 1.8:1, and grind at 35-45℃ for 1.5-2.5 hours until the fineness is ≤15μm; Secondary grinding: In the initial stage of grinding, add aziridine crosslinking agent for crosslinking activation, replace with 0.3-0.5mm zirconia beads, and grind at 25-35℃ for 1.5-3 hours under the condition of adding pH adjuster to control pH 7.5-8.5; S4. Additive curing: Add the quaternary light stabilizer, leveling agent, silicone defoamer and remaining solvent, and cure at 600-800 rpm for 1-1.5 hours. S5. Vacuum degassing: Degas for 40-60 minutes under a vacuum of -0.095 to -0.1 MPa, and then filter through a 5-10 μm filter bag; S6. Stepped curing: Use programmed temperature rise for segmented heat preservation.
[0048] Specifically, resin activation promotes uniform resin dispersion and activation, thereby improving the stability and dispersibility of the color paste; pigment dispersion improves the color uniformity and gloss of the coating; primary grinding in the stepped grinding process initially reduces pigment particle size and improves dispersion uniformity, while secondary grinding further refines pigment particle size and forms a high-density cross-linked network, thereby improving the coating's adhesion strength and flexibility; additive curing improves the coating's resistance to light aging, leveling, and defoaming effect; vacuum degassing removes air bubbles from the color paste and improves the surface quality of the coating, thereby reducing pinholes and bubble defects; and stepped curing further promotes chemical reactions and improves color paste stability, thereby improving coating performance and extending coating service life.
[0049] See appendix Figure 1 In step S1, the amount of composite solvent used is 60-70% of the total amount of solvent, the mixing temperature is 40-50℃, the stirring speed is 1000-1200rpm, and the processing time is 30-40 minutes.
[0050] Specifically, by controlling the amount of composite solvent, the viscosity and solubility of the composite resin system are adjusted, thereby optimizing the resin activation and dispersion effect. By maintaining a suitable mixing temperature, the compatibility and dissolution rate between the composite resin system and the composite solvent are promoted. By controlling the stirring speed, the composite resin system and the composite solvent are ensured to be fully mixed and dispersed, thereby improving the uniformity of resin activation and reducing agglomerates.
[0051] See appendix Figure 1 In step S3, the pH adjuster added during the secondary grinding stage is 2-amino-2-methyl-1-propanol, and the amount added is 0.1-0.5% of the total weight of the pigment paste.
[0052] Specifically, by adjusting the pH, the effects of optimizing pigment dispersion stability and improving pigment-resin compatibility were achieved.
[0053] See appendix Figure 1 In step S3, both primary grinding and secondary grinding are carried out in a horizontal nano-sand mill, and a circulating cooling system is used to control the temperature rise of the grinding material to ≤5℃.
[0054] Specifically, the horizontal nano-sand mill can provide efficient dispersion and grinding effects, especially for nano-sized pigment particles, which can achieve more uniform dispersion and finer particle size distribution; the material temperature rise is controlled within 5℃ to avoid thermal degradation of resin or pigment caused by high temperature, maintain the original performance of the color paste, and extend the service life of the product.
[0055] See appendix Figure 1 In step S2, the temperature is raised to 55-60℃, the dispersion speed is 1800-2200rpm, and the processing time is 50-70 minutes.
[0056] Specifically, increasing the temperature helps reduce the viscosity of the composite resin system, making the pigment easier to disperse. It also promotes the interaction between the pigment and the resin, improves the wettability of the pigment, and appropriate temperature can reduce shear force loss during dispersion, thereby improving dispersion efficiency.
[0057] See appendix Figure 1 In step S6, the step-cooking process is as follows: in the first stage, the temperature is increased to 45℃ at 1℃ / min and held for 4 hours; in the second stage, the temperature is increased to 60℃ at 0.5℃ / min and held for 24-40 hours.
[0058] Specifically, slowly heating to 45°C helps avoid instability in the color paste performance caused by rapid temperature changes, such as pigment agglomeration or resin phase separation; a slower heating rate of 0.5°C / min helps to further reduce the impact of temperature changes on the stability of the color paste, ensuring the performance of the color paste at high temperatures.
[0059] Example 1 This application provides a high color fastness color paste, which comprises the following components by weight: Composite resin system: 55 parts, wherein the mass ratio of epoxy acrylate, silicone-modified polyurethane, fluorinated acrylate and modified polyurethane acrylate is 5.5:3:1:1.5; Core-shell structured composite pigment: 27 parts, of which titanium dioxide base, sequentially coated with a nano-alumina layer and a zirconium oxide / cerium oxide composite layer, the mass ratio of zirconium oxide to cerium oxide is 1:0.45, the total coating thickness is 75nm, and the surface is treated with γ-glycidyl oxypropyltrimethoxysilane. The quaternary light-stabilized composition consists of 5 parts, wherein the mass ratio of benzotriazole UV absorber, dibenzophenone UV absorber, hindered amine light stabilizer, and hindered phenolic antioxidant is 4.25:3:2.4:1.15.
[0060] Multifunctional dispersant: 2.25 parts; Aziridine crosslinking agent: 3.75 parts; Leveling control agent: 1.15 parts; Organosilicon defoamer: 0.75 parts; Composite solvent: 25 parts, wherein the volume ratio of propylene glycol methyl ether acetate, isophorone, and S-150A is 2:1:0.2; the processing technology of the above-mentioned high color fastness color paste includes the following steps: S1. Resin activation: Mix the composite resin system with the composite solvent, add a multifunctional dispersant, and stir at 1100 rpm for 35 minutes at 45°C. S2. Pigment dispersion: Add core-shell structured composite pigment, heat to 57.5℃ and disperse at high speed of 2000 rpm for 55 minutes; S3, graded grinding: Primary grinding: Using 1.0mm zirconia beads at a bead-to-material mass ratio of 1.5:1, grinding at 40℃ for 2 hours until the fineness is ≤15μm; Secondary grinding: Adding aziridine crosslinking agent at the initial stage of grinding, replacing the 0.4mm zirconia beads, adding 0.3wt% 2-amino-2-methyl-1-propanol pH adjuster to control pH=8.0, grinding at 30℃ for 2.25 hours; S4. Additive curing: Add the quaternary light stabilizer, leveling agent, silicone defoamer and remaining solvent, and cure at 700 rpm for 1.25 hours; S5, Vacuum degassing: Degassing at -0.097MPa vacuum for 50 minutes, then filtering through a 7.5μm filter bag; S6. Stepped curing: In the first stage, the temperature is increased to 45℃ at 1℃ / min and held for 4 hours. In the second stage, the temperature is increased to 60℃ at 0.5℃ / min and held for 32 hours.
[0061] The high colorfastness coating process for Oxford cloth includes the following steps: S1. Padding treatment: The Oxford cloth is immersed in the color paste for 30 seconds, and the liquid carry-over rate is controlled at 65% by uniform rolling. S2. Preliminary curing: Dry with hot air at 105℃ for 4 minutes to form the initial film layer; S3, High-temperature crosslinking: Heat treatment at 145℃ for 89 minutes activates the aziridine crosslinking agent to complete deep crosslinking; S4. Post-curing: 24 hours of room temperature equilibration to stabilize the bonding between the membrane and the fiber.
[0062] Example 2 This application provides a high color fastness color paste, which comprises the following components by weight: Composite resin system: 65 parts, wherein the mass ratio of epoxy acrylate, silicone-modified polyurethane, fluorinated acrylate and modified polyurethane acrylate is 7:2:0.5:1; Core-shell structured composite pigment: 35 parts, consisting of a titanium dioxide base, sequentially coated with a nano-alumina layer and a zirconium oxide / cerium oxide composite layer, with a zirconium oxide to cerium oxide mass ratio of 1:0.6, a total coating thickness of 100 nm, and a surface treated with γ-glycidyl etheroxypropyltrimethoxysilane. A quaternary light-stabilized composition: 6 parts, wherein the mass ratio of benzotriazole UV absorber, dibenzophenone UV absorber, hindered amine light stabilizer and hindered phenolic antioxidant is 5:2.5:1.8:0.8; Multifunctional dispersant: 3 parts; Aziridine crosslinking agent: 5 parts; Leveling control agent: 1.5 parts Organosilicon defoamer: 1 part; Composite solvent: 30 parts, wherein the volume ratio of propylene glycol methyl ether acetate, isophorone and S-150A is 3:1:0.3.
[0063] The processing technology for the above-mentioned high color fastness color paste includes the following steps: S1. Resin activation: The composite resin system is mixed with the composite solvent, a multifunctional dispersant is added, and the mixture is stirred at 1200 rpm for 30 minutes at 50°C. S2. Pigment dispersion: Add pigment, heat to 60℃ and disperse at high speed of 2200 rpm for 50 minutes; S3, graded grinding: Primary grinding: Using 1.2mm zirconia beads at a bead-to-material mass ratio of 1.8:1, grind at 45℃ for 1.5 hours until the fineness is ≤15μm; Secondary grinding: Add aziridine crosslinking agent, replace 0.3mm zirconia beads, add 0.5wt% 2-amino-2-methyl-1-propanol pH adjuster, control pH=8.5, and grind at 25℃ for 3 hours; S4. Additive curing: Add the quaternary light stabilizer, leveling agent, silicone defoamer and remaining solvent, and cure at 800 rpm for 1 hour; S5, Vacuum degassing: Degas for 40 minutes under a vacuum of -0.1MPa, then filter through a 5μm filter bag; S6. Stepped curing: In the first stage, the temperature is increased to 45℃ at 1℃ / min and held for 4 hours. In the second stage, the temperature is increased to 60℃ at 0.5℃ / min and held for 40 hours.
[0064] The high colorfastness coating process for Oxford cloth includes the following steps: exactly the same as in Example 1.
[0065] Example 3 This application provides a high color fastness color paste, which comprises the following components by weight: Composite resin system: 45 parts, wherein the mass ratio of epoxy acrylate, silicone-modified polyurethane, fluorinated acrylate and modified polyurethane acrylate is 4:4:1.5:2; Core-shell structured composite pigment: 20 parts, of which titanium dioxide base, sequentially coated with a nano-alumina layer and a zirconium oxide / cerium oxide composite layer, the mass ratio of zirconium oxide to cerium oxide is 1:0.3, the total coating thickness is 50nm, and the surface is treated with γ-glycidyl oxypropyltrimethoxysilane; The quaternary light-stabilized composition consists of 4 parts, wherein the mass ratio of benzotriazole UV absorber, dibenzophenone UV absorber, hindered amine light stabilizer, and hindered phenolic antioxidant is 3.5:3.5:3:1.5. Multifunctional dispersant: 1.5 parts; Aziridine crosslinking agent: 2.5 parts; Leveling control agent: 0.8 parts; Organosilicon defoamer: 0.5 parts Composite solvent: 20 parts, wherein the volume ratio of propylene glycol methyl ether acetate, isophorone and S-150A is 1:1:0.1.
[0066] The processing technology for the above-mentioned high color fastness color paste includes the following steps: S1. Resin activation: The composite resin system is mixed with the composite solvent, a multifunctional dispersant is added, and the mixture is stirred at 1000 rpm for 40 minutes at 40°C. S2. Pigment dispersion: Add core-shell structured composite pigment, heat to 55℃ and disperse at high speed of 1800 rpm for 70 minutes. S3, graded grinding: Primary grinding: Using 0.8mm zirconia beads at a bead-to-material mass ratio of 1.2:1, grind at 35℃ for 2.5 hours until the fineness is ≤15μm; Secondary grinding: Add aziridine crosslinking agent, replace 0.5mm zirconia beads, add 0.1wt% 2-amino-2-methyl-1-propanol pH adjuster, control pH=7.5, and grind at 35℃ for 1.5 hours; S4. Additive curing: Add the quaternary light stabilizer, leveling agent, silicone defoamer and remaining solvent, and cure at 600 rpm for 1.5 hours; S5, Vacuum degassing: Degassing at -0.095MPa vacuum for 60 minutes, then filtering through a 10μm filter bag; S6. Stepped curing: In the first stage, the temperature is increased to 45℃ at 1℃ / min and held for 4 hours. In the second stage, the temperature is increased to 60℃ at 0.5℃ / min and held for 24 hours.
[0067] The high colorfastness coating process for Oxford cloth includes the following steps: exactly the same as in Example 1.
[0068] Comparative Example 1 This comparative example provides a high color fastness color paste, the only difference between its composition and that of Example 1 is the ratio of the quaternary light-stabilized composition. In this light-stabilized composition, the mass ratio of benzotriazole, benzophenone, hindered amine, and hindered phenol is 2:5:0.5:1.5. The total amount remains 5 parts.
[0069] The processing steps of the above-mentioned high color fastness color paste are exactly the same as those in Example 1.
[0070] The high colorfastness coating process for Oxford cloth includes the following steps: exactly the same as in Example 1.
[0071] Comparative Example 2 This comparative example provides a high color fastness color paste, the only difference of which is that the composite resin system does not contain fluorinated acrylate, and its proportions are allocated to other resins.
[0072] Composite resin system: 55 parts, wherein epoxy acrylate: silicone-modified polyurethane: modified polyurethane acrylate = 6.5:3.5:2, and 1 part of the original fluorinated acrylate is added to epoxy acrylate and modified polyurethane acrylate by mass ratio; other components are the same as in Example 1.
[0073] The processing steps of the above-mentioned high color fastness color paste are exactly the same as those in Example 1.
[0074] Comparative Example 3 This comparative example provides a high color fastness color paste, the only difference of which is the composition ratio of the paste compared with that of Example 1: the core-shell structured composite pigment is replaced with uncoated pure titanium dioxide with a particle size of 200 nm and without silane treatment.
[0075] The processing steps of the above-mentioned high color fastness color paste are exactly the same as those in Example 1.
[0076] S1, Same as Example 1; S2. Pigment dispersion: Add uncoated titanium dioxide, heat to 57.5℃ and disperse at 2000 rpm for 40 minutes; S3-S6, same as in Example 1.
[0077] The high colorfastness coating process for Oxford cloth includes the following steps: exactly the same as in Example 1.
[0078] Comparative Example 4 This comparative example provides a high color fastness color paste, the only difference between its composition and that of Example 1 is that the composite resin system does not contain modified polyurethane acrylate, but is allocated to silicone-modified polyurethane.
[0079] Composite resin system: 55 parts, wherein epoxy acrylate: silicone-modified polyurethane: fluorinated acrylate = 5.5:4.5:1, and 1.5 parts of the original modified polyurethane acrylate are added to the silicone-modified polyurethane; other components are the same as in Example 1.
[0080] The processing steps of the above-mentioned high color fastness color paste are exactly the same as those in Example 1.
[0081] Table 1 shows the summary data of the high color fastness type color paste performance test of Examples 1-3 and Comparative Examples 1-4.
[0082] Table 1: As can be seen from Examples 1-3 and Comparative Example 1, and Table 1, the imbalance in the ratio of the quaternary light-stabilizing composition leads to insufficient benzotriazole ultraviolet absorbers, which in turn causes the 300h xenon lamp aging ΔE to increase from 1.2 to 2.1, an increase of 75%, demonstrating the necessity of a specific ratio for light stability.
[0083] Combining Examples 1-3 and Comparative Example 2 with Table 1, it can be seen that after removing the fluorinated acrylate component from the composite resin, the flexibility deteriorated precipitously, the axial bending test only passed at φ6mm, and the wet rubbing color fastness dropped from grade 4 to grade 3, exposing the dual beneficial effect of the fluorinated chain segment on dynamic flexibility and interfacial abrasion resistance.
[0084] Combining Examples 1-3 and Comparative Example 3 with Table 1, it can be seen that the absence of the core-shell composite coating layer leads to the failure of acid etching protection, which in turn causes the ΔE of 5% H2SO4 immersion to increase from 0.6 to 2.3, an increase of 283%, and the wet rubbing color fastness to plummet from level 4 to level 2-3, proving that the proton shielding effect of the 75nm coating layer is irreplaceable.
[0085] Combined with Examples 1-3 and Comparative Example 4 and Table 1, it can be seen that removing the modified polyurethane acrylate caused resin phase separation, and the ΔE increased from 1.2 to 1.9 after 300h aging, and the adhesion deteriorated from grade 0 to grade 1, proving that its carboxyl functional group is irreplaceable for resin compatibility and coating-substrate anchoring force.
[0086] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high color fastness color paste, characterized in that: The following components are included by weight: 45-65 parts of composite resin system; 20-35 parts of core-shell structured composite pigment; 4-6 parts of quaternary light-stabilized composition; 1.5-3 parts of multifunctional dispersant; 2.5-5 parts of aziridine crosslinking agent; 0.8-1.5 parts of leveling control agent; 0.5-1 part of silicone defoamer; 20-30 parts of composite solvent; The composite resin system consists of epoxy acrylate, silicone-modified polyurethane, fluorinated acrylate, and modified polyurethane acrylate, with a mass ratio of 4-7:2-4:0.5-1.5:1-2. The core-shell structured composite pigment is iron oxide red or titanium dioxide sequentially coated with a nano-alumina layer and a composite layer composed of zirconium oxide and cerium oxide in a mass ratio of 1:0.3-0.6, and the surface is treated with γ-glycidyl etheroxypropyltrimethoxysilane, with a total coating layer thickness of 50-100 nm. The quaternary light-stabilizing composition consists of benzotriazole UV absorbers, benzophenone UV absorbers, hindered amine light stabilizers, and hindered phenolic antioxidants.
2. The high color fastness color paste according to claim 1, characterized in that: The mass ratio of benzotriazole UV absorber, benzophenone UV absorber, hindered amine light stabilizer and hindered phenolic antioxidant in the quaternary light-stabilized composition is 3.5-5:2.5-3.5:1.8-3:0.8-1.
5.
3. The high color fastness color paste according to claim 2, characterized in that: The hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the hindered amine light stabilizer is poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol) ester.
4. The high color fastness color paste according to claim 1, characterized in that: The composite solvent is composed of propylene glycol methyl ether acetate, isophorone and high-boiling-point aromatic solvent S-150A, with a volume ratio of 1-3:1:0.1-0.
3.
5. A processing technology for a high color fastness color paste, characterized in that, A high color fastness color paste according to any one of claims 1-4 includes the following steps: S1. Resin activation: Mix the composite resin system with a portion of the composite solvent, add a multifunctional dispersant and stir to dissolve; S2, Pigment Dispersion: Add core-shell structured composite pigments, heat and perform high-speed shear dispersion; S3, graded grinding: Primary grinding: Use 0.8-1.2mm zirconia beads, with a bead-to-material ratio of 1.2:1 to 1.8:1, and grind at 35-45℃ for 1.5-2.5 hours until the fineness is ≤15μm; Secondary grinding: In the initial stage of grinding, add aziridine crosslinking agent for crosslinking activation, replace with 0.3-0.5mm zirconia beads, and grind at 25-35℃ for 1.5-3 hours under the condition of adding pH adjuster to control pH 7.5-8.5; S4. Additive curing: Add the quaternary light stabilizer, leveling agent, silicone defoamer and remaining solvent, and cure at 600-800 rpm for 1-1.5 hours. S5. Vacuum degassing: Degas for 40-60 minutes under a vacuum of -0.095 to -0.1 MPa, and then filter through a 5-10 μm filter bag. S6. Stepped ripening: Segmented heat preservation is carried out by programmed heating.
6. The processing technology of a high color fastness type color paste according to claim 5, characterized in that: In step S1, the amount of the composite solvent used is 60-70% of the total solvent, the mixing temperature is 40-50℃, the stirring speed is 1000-1200rpm, and the processing time is 30-40 minutes.
7. The processing technology of a high color fastness color paste according to claim 5, characterized in that: In step S3, the pH adjuster added in the secondary grinding stage is 2-amino-2-methyl-1-propanol, and the amount added is 0.1-0.5% of the total weight of the pigment paste.
8. The processing technology of a high color fastness color paste according to claim 5, characterized in that: In step S3, both the primary grinding and the secondary grinding are carried out in a horizontal nano-sand mill, and a circulating cooling system is used to control the temperature rise of the grinding material to ≤5℃.
9. The processing technology of a high color fastness type color paste according to claim 5, characterized in that: In step S2, the temperature is raised to 55-60℃, the dispersion speed is 1800-2200rpm, and the processing time is 50-70 minutes.
10. The processing technology of a high color fastness type color paste according to claim 5, characterized in that: In step S6, the stepped curing process is as follows: in the first stage, the temperature is increased to 45°C at 1°C / min and held for 4 hours; in the second stage, the temperature is increased to 60°C at 0.5°C / min and held for 24-40 hours.
